A method of screening high density solution titanium alloy articles

CN120838559BActive Publication Date: 2026-10-27SICHUAN SCI CITY JIULI TECH IND CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511161508.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2026-10-27
Estimated Expiration
2045-08-19

AI Technical Summary

Technical Problem

[0003]一方面,逐颗称量的操作模式使得筛选效率受限于人工操作速度,单颗处理耗时长达3-5秒,单日最大处理量难以突破15000颗,严重制约了生产节拍;另一方面,长时间重复性操作不仅大幅提升了操作人员的劳动强度,还易因人为疲劳导致误判率上升

Benefits of technology

[0042]1.本申请通过利用自制的高密度基础溶液(毒性低,危险级别为8级)的透明特性,便于实时观察钛合金颗粒浮沉状态,操作安全且直观;全程无需人工逐颗操作,仅通过溶液中浮沉状态即可实现大批量钛合金颗粒的快速分选,有效解决了现有技术中筛选效率低的问题,显著降低操作人员劳动强度,适配规模化生产需求,且该方法专用于钛合金颗粒筛选,不适用同类或其他产品。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005555385300000071
    Figure BDA0005555385300000071
Patent Text Reader

Abstract

The application discloses a high-density solution titanium alloy product screening method and belongs to the technical field of titanium alloy product screening. The method is based on the principle of density difference separation, and batch screening is realized through twice screening: in the first screening, titanium alloy particles to be screened are added into a high-density base solution (composed of phosphoric acid, sodium phosphate and sodium carbonate) with a density of 1.65 g / cm 3 , and the particles with excessively large density that sink to the bottom are removed; in the second screening, the particles that float or suspend in the first screening are added into a solution with a density adjusted to 1.48 g / cm 3 , and the particles that sink to the bottom or suspend are qualified products. The application utilizes the transparent characteristics of the high-density solution to facilitate observation, and large batch screening can be realized without operating on each particle, so that the efficiency is improved, the labor intensity is reduced, the method is suitable for large-scale production, and after screening, a step-by-step cleaning step is adopted to remove residual solution, the titanium phosphate film formed on the surface of the titanium alloy is protected, and the stability of the product is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of titanium alloy product screening technology, specifically a high-density solution titanium alloy product screening method. Background Technology

[0002] In the industrial mass production of titanium alloy particles, screening for quality uniformity in large batches is a crucial step in determining the performance stability of the final product. Currently, the mainstream screening method in the industry relies on high-precision electronic balances to weigh each particle individually, using weight deviation to determine product qualification. While this method meets basic accuracy requirements, its inherent shortcomings become increasingly apparent in large-scale production scenarios (such as daily processing volumes exceeding 10,000 particles).

[0003] On the one hand, the weighing operation mode limits the screening efficiency to the speed of manual operation, with each piece taking 3-5 seconds to process, making it difficult to exceed 15,000 pieces per day, which seriously restricts the production cycle. On the other hand, the long-term repetitive operation not only greatly increases the labor intensity of the operators, but also easily leads to an increase in the misjudgment rate due to human fatigue.

[0004] Studies have shown that the density of qualified titanium alloy particles exists within a strict range (1.48 g / cm³). 3 -1.65g / cm 3 This characteristic makes non-contact batch screening possible.

[0005] Therefore, developing a high-efficiency screening technology based on density differences to replace traditional weighing methods has become a key issue in overcoming existing production bottlenecks and achieving large-scale screening. Summary of the Invention

[0006] The purpose of this invention is to provide a high-density solution screening method for titanium alloy products. This invention is based on the density difference sorting principle, utilizes the low toxicity and transparency of a specially formulated high-density solution, and ensures accurate screening through standard particle calibration. It eliminates the need for manual particle-by-particle operation, enabling large-scale screening, improving efficiency, reducing labor intensity, and is suitable for large-scale production screening of titanium alloy particles.

[0007] The objective of this invention is achieved through the following technical solution:

[0008] A method for screening high-density solution-treated titanium alloy products includes the following steps:

[0009] S1. First screening: Select samples with a density of 1.65 g / cm³. 3 A high-density base solution is added to the first open container, and then the titanium alloy particles to be screened are added to the first open container without accumulation.

[0010] S2. Second screening: Take another high-density basic solution and add it to the second open container, followed by adding a solution with a density of 1.48 g / cm³. 3 Standard titanium alloy particles are then added to a second open container, and water is added until the standard titanium alloy particles are suspended. After that, the floating or suspended titanium alloy particles in step S1 are taken out and added to the second open container. The titanium alloy particles that sink or remain suspended after standing are the qualified products selected.

[0011] The high-density base solution is composed of phosphoric acid, sodium phosphate, and sodium carbonate.

[0012] This application, based on the principle of density difference sorting, achieves batch screening by preparing two solutions with precisely controllable densities (corresponding to the upper and lower limits of the density of qualified titanium alloy particles, respectively):

[0013] The first step uses a high-density solution (1.65 g / cm³). 3 Remove items with excessive density (>1.65 g / cm³). 3 For substandard products, the second step involves using a low-density solution (1.48 g / cm³). 3 Remove those with excessively low density (<1.48 g / cm³). 3 Of the substandard products, those with a density of 1.48–1.65 g / cm³ were ultimately retained. 3 The titanium alloy particles are qualified products. During this process, the titanium alloy particles react chemically with phosphoric acid in the high-density base solution to form a dense titanium phosphate film on the surface, which enhances the corrosion resistance of the titanium alloy.

[0014] Compared to the existing method of weighing each particle individually, this method can process large batches of titanium alloy particles at once, effectively improving screening efficiency and meeting the needs of large-scale production.

[0015] As some possible embodiments of this application, the high-density base solution is composed of 60 wt% phosphoric acid, 15 wt% sodium phosphate, and 25 wt% sodium carbonate.

[0016] As some possible implementations of this application, in steps S1 and S2, after the high-density base solution is poured into the container, the liquid level is 10-15 mm from the bottom of the first open container. By limiting the distance between the liquid level and the bottom wall of the container, it can be ensured that the liquid depth can completely submerge the titanium alloy particles while avoiding disturbance caused by excessive liquid level.

[0017] As some possible implementations of this application, in steps S1 and S2, the solution density is checked with the corresponding standard particles after each screening. If the floating or sinking state of the standard particles changes, water is added in time to adjust it to the standard state to ensure the accuracy of screening.

[0018] As one possible implementation of this application, after the titanium alloy particles that have sunk to the bottom or are suspended are retrieved in step S2, the following steps are performed:

[0019] S3. Cleaning:

[0020] S31. First-level cleaning: Transfer the titanium alloy particles to a rotary cleaning tank and spray them with deionized water from all directions.

[0021] During the first-stage cleaning, the free high-density solution (including unreacted phosphoric acid, sodium phosphate, and sodium carbonate) adhering to the surface of titanium alloy particles can be quickly rinsed away through the all-round spray of the rotating cleaning tank. This effectively prevents these residual solutions from crystallizing after drying. The crystallized salts (such as Na3PO4) will mechanically damage the dense structure of the titanium phosphate film, leading to micropores or cracks in the film layer.

[0022] S32. Secondary cleaning: Prepare a deionized aqueous solution containing 0.08-0.13wt% EDTA-2Na and 0.04-0.06wt% nonionic surfactant (such as Tween-80) as the cleaning solution, immerse the titanium alloy particles in it for 1-1.5 minutes; then rinse with deionized water.

[0023] In the secondary cleaning process, EDTA-2Na is a strong complexing agent that can react with residual Na in the high-density solution. + Ti 4+ (The trace amounts of dissolution on the surface of the titanium phosphate film produce) a stable complex, which prevents these ions from depositing on the film surface and forming "salt bloom";

[0024] Nonionic surfactants can reduce the surface tension of the solution, enhance the wetting ability of the cleaning solution on the surface and micropores of the titanium phosphate film, make the complexing agent more easily penetrate into the gaps, and improve the ion removal efficiency.

[0025] S33. Three-stage cleaning: Add deionized water to the ultrasonic cleaning tank, add 0.1-0.2wt% of nonionic surfactant (such as Tween-80), put the titanium alloy particles into it, and use pulsed ultrasonic treatment;

[0026] In the three-stage cleaning process, surfactants emulsify and disperse impurities, reducing their adhesion to the membrane. The cavitation effect generated by pulsed ultrasound can strip away these impurities, and because the pulsed mode has a gentle impact force, it will not cause mechanical damage to the titanium phosphate membrane. Pulsed ultrasound combined with nonionic surfactants can specifically remove tiny impurities (such as undissolved sodium phosphate particles) attached to the surface and micropores of the titanium phosphate membrane.

[0027] S34. Level 4 cleaning: Use deionized water with a resistivity ≥18MΩ·cm to spray and finely clean the particles;

[0028] In the fourth-stage cleaning process, high-purity deionized water spraying and rinsing thoroughly removes trace amounts of cleaning solutions (such as EDTA-2Na and surfactants) remaining from the first three steps. If these residual cleaning solutions are not removed, they will form an organic film on the surface of the titanium phosphate film after drying, affecting the film's corrosion resistance (the film easily absorbs moisture, forming a localized electrolyte).

[0029] S35. Drying treatment: Vacuum dry the cleaned titanium alloy particles.

[0030] Vacuum drying accelerates moisture evaporation through negative pressure, and combined with drying nitrogen purging, it can quickly remove residual moisture from the surface and interior (such as hollow structures) of titanium alloy particles. This effectively prevents moisture from forming an electrolyte with unremoved trace amounts of salt (such as Na2CO3). This electrolyte can penetrate into the titanium alloy matrix through the micropores of the titanium phosphate film, leading to localized corrosion (rust spots).

[0031] In summary, this application achieves comprehensive removal of residual high-density solution (containing phosphoric acid, sodium phosphate, and sodium carbonate) from the surface and micropores of titanium alloy particles through a step-by-step treatment process of "first-stage rinsing → second-stage complexation → third-stage ultrasonication → fourth-stage fine washing → vacuum drying," while simultaneously protecting the titanium phosphate film (dense protective layer) formed during the screening process. Specifically, the synergistic effect of each step not only avoids corrosion of the film layer by residual salt crystallization but also enhances the protection against metal ions (such as sodium carbonate) through targeted processes (such as complexation and pulsed ultrasonication). + This improves the cleaning efficiency of titanium alloy particles and ultimately enhances the surface cleanliness and integrity retention of the titanium phosphate film after cleaning, providing a stable protective foundation for subsequent transportation, storage and use.

[0032] As some possible implementations of this application, in step S31, a 5-8mm thick food-grade silicone mesh pad is laid on the inner bottom and inner wall of the rotary cleaning tank; the cleaning tank rotates at a speed of 15-20r / min, and the spraying duration is 40-50s.

[0033] In this solution, the food-grade silicone mesh pad has moderate elasticity, which can buffer the impact force of titanium alloy particles during rotation and tumbling, effectively reducing the degree of damage to the titanium phosphate film due to mechanical friction.

[0034] The rotation speed of 15-20 r / min and the spraying time of 40-50 s are matched to ensure that the outer surface, grooves and micropores are thoroughly rinsed through particle tumbling, while avoiding particle accumulation due to excessive rotation speed. This increases the surface free solution removal rate to over 98% and reduces the load of subsequent secondary cleaning.

[0035] As some possible implementations of this application, in step S33, the parameters of the pulsed ultrasonic treatment are: power of 150-180W, ultrasonic time of 2-5min (3s ultrasonic + 1s pause), and water temperature of 30±2℃.

[0036] In this scheme, the 150-180W power and pulsed operating mode can reduce the impact of ultrasonic cavitation on the titanium phosphate film (the film thickness is about 50-100nm, and its impact resistance is relatively weak). At the same time, the processing time of 2-5 minutes is sufficient to remove residual complexes and tiny impurities in the micropores. Meanwhile, pulsed ultrasound reduces continuous vibration impact, which can reduce the incidence of microcracks in thin-walled particles.

[0037] As some possible implementations of this application, in step S34, the parameters for spray cleaning are: spray pressure of 0.3-0.4 MPa and spray time of 30-40 s.

[0038] In this method, a spray pressure of 0.3-0.4 MPa generates a strong impact force, effectively stripping away trace amounts of residual EDTA-2Na, surfactants, and other cleaning solution components from the surface, preventing them from forming a thin film that masks defects in the titanium phosphate film after drying. Simultaneously, the short spray time of 30-40 seconds ensures that high-purity deionized water fully contacts the particle surface while avoiding erosion damage to the titanium phosphate film caused by prolonged high pressure.

[0039] As some possible implementations of this application, in step S35, the parameters for vacuum drying are: under conditions of -0.08 to 0.1 MPa and 50 to 55°C, a drying nitrogen gas with a flow rate of 1 to 2 L / min is introduced for purging, and the drying time is 10 to 15 min.

[0040] In this design, the low-temperature (50-55℃) vacuum environment will not cause thermal damage to the titanium phosphate film (the film has limited high-temperature resistance and is prone to structural loosening above 60℃), ensuring that the film maintains its density and protective performance. At the same time, nitrogen purging can isolate oxygen and moisture in the air, preventing the film from being oxidized during the drying process.

[0041] Compared with the prior art, the beneficial effects of the present invention are:

[0042] 1. This application utilizes the transparency of a self-made high-density base solution (low toxicity, hazard level 8) to facilitate real-time observation of the floating and sinking status of titanium alloy particles, making the operation safe and intuitive. The entire process eliminates the need for manual handling of each particle individually; large-scale rapid sorting of titanium alloy particles can be achieved solely through observation of their floating and sinking status in the solution. This effectively solves the problem of low screening efficiency in existing technologies, significantly reduces the labor intensity of operators, and is suitable for large-scale production needs. Furthermore, this method is specifically designed for titanium alloy particle screening and is not applicable to similar or other products.

[0043] 2. This application employs a step-by-step treatment process—"first-stage rinsing → second-stage complexation → third-stage ultrasonication → fourth-stage fine washing → vacuum drying"—to achieve comprehensive removal of residual high-density solutions (containing phosphoric acid, sodium phosphate, and sodium carbonate) from the surface and micropores of titanium alloy particles, while simultaneously protecting the titanium phosphate film (dense protective layer) formed during the screening process. Specifically, the synergistic effect of each step avoids corrosion of the film layer by residual salt crystallization and enhances the protection against metal ions (such as sodium carbonate) through targeted processes (such as complexation and pulsed ultrasonication). + This improves the cleaning efficiency of titanium alloy particles and ultimately enhances the surface cleanliness and integrity retention of the titanium phosphate film after cleaning, providing a stable protective foundation for subsequent transportation, storage and use. Detailed Implementation

[0044] Example 1

[0045] S1. Preparation of high-density base solution: Mix 60wt% phosphoric acid, 15wt% sodium phosphate, and 25wt% sodium carbonate to prepare a solution with a density of 1.65 g / cm³. 3 High-density base solution;

[0046] S2. First screening: Add the above high-density base solution to the first open container, with the liquid level 12mm from the bottom of the container; take 300 titanium alloy particles to be screened, add them evenly to the container (without accumulation), let stand for 5 minutes, and remove the floating or suspended particles (205 particles, density ≤1.65g / cm³). 3 Remove 95 particles that sink to the bottom (density > 1.65 g / cm³). 3 );

[0047] S3. Second screening: Add high-density base solution (liquid level 12mm from bottom) to the second open container, and add a solution with a density of 1.48g / cm³. 3 Standard titanium alloy particles were added to water until they were suspended (at which point the solution density was 1.48 g / cm³). 3 Add the 205 particles scooped out in step S2 to the second container, let stand for 5 minutes, and the 172 particles that sink or remain suspended are considered qualified (density 1.48-1.65 g / cm³). 3 ), removing floating particles (33 particles, density <1.48 g / cm³). 3 ).

[0048] Results: 172 samples were qualified, with density tests showing all samples ranged from 1.48 to 1.65 g / cm³. 3 Within this range, the density, calculated by sampling and weighing, is consistently between 0.88 and 0.93 g / cm³. 3 Within the specified range, the accuracy is 100%; the screening time for a single batch is ≤30 minutes, which is more efficient than weighing each particle individually (the traditional method requires at least 2 hours).

[0049] Example 2

[0050] 183 qualified samples were obtained according to the screening method in Example 1, and then the qualified samples were cleaned as follows:

[0051] S31. First-level cleaning: Transfer 183 particles to a rotary cleaning tank (with a 6mm thick food-grade silicone mesh pad on the inner wall and bottom), spray with deionized water (flow rate 9L / min) from all directions, and rotate the cleaning tank at 18r / min for 45s.

[0052] S32. Secondary cleaning: Prepare a deionized water solution containing 0.1 wt% EDTA-2Na and 0.05 wt% Tween-80, soak the particles for 1.2 min, and then rinse twice with deionized water (3 min each time);

[0053] S33. Three-stage cleaning: Add deionized water and 0.15wt% Tween-80 to the ultrasonic tank, put in the particles, and use pulsed ultrasound (power 160W, 3s ultrasound + 1s pause, time 3min, water temperature 30℃).

[0054] S34. Level 4 cleaning: Spray with deionized water with a resistivity of 18.2 MΩ·cm at a pressure of 0.35 MPa for 35 seconds;

[0055] S35. Vacuum drying: Under conditions of -0.09MPa and 52℃, purge with drying nitrogen gas at a rate of 1.5L / min for 12min.

[0056] Example 3

[0057] 170 qualified samples were obtained according to the screening method in Example 1. The qualified samples were then cleaned, and the immersion method was adjusted compared to Example 2 as follows:

[0058] S31. Silicone mesh pad 5mm thick, cleaning tank rotates at 15r / min, spraying for 40s (flow rate 8L / min);

[0059] S32. The cleaning solution contains 0.08wt% EDTA-2Na and 0.04wt% Tween-80. Soak for 1 minute and rinse twice.

[0060] S33. Ultrasonic power 150W, time 2.5min, water temperature 28℃;

[0061] S34. Spray pressure 0.3MPa, time 30s;

[0062] S35. Vacuum drying: -0.08MPa, 50℃, nitrogen flow rate 1L / min, time 10min.

[0063] The remaining steps and parameters are the same as in Example 2.

[0064] Comparative Example 1 (replacing the secondary cleaning complexing agent)

[0065] 185 qualified samples were obtained according to the method in Example 1, and then cleaned. During cleaning, compared with Example 2, only S32 was adjusted to soak in a solution containing 0.25wt% trisodium citrate and 0.05wt% Tween-80 for 1.2 min, while other parameters remained unchanged.

[0066] Comparative Example 2

[0067] The screening steps are the same as in Example 1 (168 qualified products were obtained), and the subsequent cleaning process is as follows:

[0068] S1. Neutralization treatment: Transfer 168 particles to a neutralization tank, add 0.8wt% sodium bicarbonate aqueous solution (room temperature, liquid level submerges particles by 5mm), turn on stirring (speed 50r / min) to disperse and suspend for 2min, then remove and drain;

[0069] S2. First-level cleaning: Transfer to the cleaning tank, spray for 10 seconds at a flow rate of 7L / min (nozzles distributed at 45°), then soak for 15 seconds, and then take out and drain.

[0070] S3. Secondary targeted cleaning:

[0071] Vacuum treatment: Place the particles into a sealed device, evacuate to -0.08MPa (15s), introduce 35℃ deionized water until the particles are submerged, maintain the pressure for 20s, and then slowly release the pressure.

[0072] Ultrasonic treatment: Transfer to an ultrasonic cleaning tank (deionized water 35℃), and continue ultrasonication at 250W power for 1 minute. Remove and drain.

[0073] S4. Drying treatment: Same as in Example 2.

[0074] Experimental Example

[0075] To verify the effectiveness of the cleaning steps of this invention, key indicators of the titanium alloy particles after cleaning in Examples 2-3 and Comparative Examples 1-2 were tested, as follows:

[0076] 1. Residual Na + Content detection.

[0077] Flame atomic absorption spectrometry was used.

[0078] Thirty titanium alloy particles were randomly cleaned and then ultrasonically extracted with deionized water (18 MΩ·cm) for 5 minutes to remove residual Na from the surface. + Completely dissolved;

[0079] Na in the extract was determined using atomic absorption spectrometry at a wavelength of 589.0 nm. +Concentration is calculated as "(concentration × volume) / total surface area" (mg / cm²). 2 ).

[0080] 2. Detection of the integrity retention rate of titanium phosphate membrane.

[0081] Combining scanning electron microscopy observation with electrochemical testing:

[0082] Ten particles were randomly selected, and after being sputter-coated with gold, the film was observed using a scanning electron microscope (5000× magnification) to check for any damage (cracks, peeling).

[0083] Select particles without visible damage and test their polarization curves in a 3.5 wt% NaCl solution. The corrosion current density is <1 × 10⁻⁶. -6 A / cm 2 That is, the membrane layer is intact;

[0084] The retention rate is calculated as "number of undamaged particles / total number of tests × 100%".

[0085] 3. Rust rate test after storage.

[0086] Simulate actual storage conditions: Randomly select 100 particles and store them in an environment of 25℃ and 60% humidity for 6 months;

[0087] When observed with an optical microscope, rust spots with a diameter >0.1 mm are identified as corrosion.

[0088] The corrosion rate is calculated as "number of rusted particles / total number of particles × 100%".

[0089] It is worth noting that the above methods are all general means of surface testing of metal materials, which can meet the evaluation requirements of the present invention for cleaning effect.

[0090] The results are shown in Table 1.

[0091] Table 1:

[0092]

[0093] As can be seen from Table 1:

[0094] 1. The density qualification rate of Examples 2-3 and Comparative Examples 1-2 was 100% (by weighing method), indicating that the screening steps of the present invention and the existing screening methods can accurately screen out titanium alloy particles with a density in the range of 1.48-1.65 g / cm3.

[0095] 2. Cleaning effect: ① In Examples 2-3, residual Na was removed through step-by-step cleaning. +The content was significantly lower than that of the comparative example, indicating that the combination of EDTA-2Na complexation and pulsed ultrasound can more thoroughly remove salt residues. Comparative example 1, due to the use of trisodium citrate, generated sodium hydrogen phosphate precipitate, resulting in a membrane coverage of only 70%. In contrast, the titanium phosphate membrane integrity retention rate of Examples 2-3 reached 99%-100%, demonstrating effective membrane protection. ② After 6 months of storage, Examples 2-3 showed extremely low corrosion rates (0-0.6%), while Comparative examples 1-2, due to residues or membrane defects, had corrosion rates reaching 25%, verifying the effectiveness of the cleaning steps in improving the long-term storage performance of the product.

[0096] In summary, the cleaning steps of this invention significantly improve the cleanliness of titanium alloy particles, the integrity of the film layer, and the storage stability, making it suitable for large-scale production needs.

Claims

1. A method for screening high-density solution-treated titanium alloy products, characterized in that, Includes the following steps: S1. First screening: A high-density base solution with a density of 1.65 g / cm³ is added to the first open container, and then the titanium alloy particles to be screened are added to the first open container without accumulation. S2. Second screening: Take another high-density basic solution and add it to the second open container, followed by adding a solution with a density of 1.48 g / cm³. 3 Standard titanium alloy particles are then added to a second open container, and water is added until the standard titanium alloy particles are suspended. After that, the floating or suspended titanium alloy particles in step S1 are taken out and added to the second open container. The titanium alloy particles that sink or remain suspended after standing are the qualified products selected. The high-density base solution is composed of 60 wt% phosphoric acid, 15 wt% sodium phosphate, and 25 wt% sodium carbonate. After removing the titanium alloy particles that have sunk to the bottom or are suspended in step S2, proceed with the following steps: S3. Cleaning: S31. First-level cleaning: Transfer the titanium alloy particles to a rotary cleaning tank and spray them with deionized water from all directions; S32. Secondary cleaning: Prepare a deionized water solution containing 0.08-0.13wt% EDTA-2Na and 0.04-0.06wt% nonionic surfactant as the cleaning solution, immerse the titanium alloy particles in it for 1-1.5 min; then rinse with deionized water. S33. Three-stage cleaning: Add deionized water and 0.1-0.2wt% nonionic surfactant to the ultrasonic cleaning tank, put the titanium alloy particles in, and treat them with pulsed ultrasonic treatment; S34. Level 4 cleaning: Use deionized water with a resistivity ≥18MΩ・cm to spray and finely clean the particles; S35. Drying treatment: Vacuum dry the cleaned titanium alloy particles.

2. The method for screening high-density solution-treated titanium alloy products according to claim 1, characterized in that, In steps S1 and S2, after the high-density base solution is poured into the container, the liquid level is 10-15 mm from the bottom of the first open container.

3. The method for screening high-density solution-treated titanium alloy products according to claim 1, characterized in that, In steps S1 and S2, the solution density is checked with the corresponding standard particles after each screening. If the floating or sinking state of the standard particles changes, water is added in time to adjust it to the standard state.

4. The method for screening high-density solution-treated titanium alloy products according to claim 1, characterized in that, In step S31, a 5-8mm thick food-grade silicone mesh pad is laid on the inner bottom and inner wall of the rotary cleaning tank; the cleaning tank rotates at a speed of 15-20r / min, and the spraying duration is 40-50s.

5. The method for screening high-density solution-treated titanium alloy products according to claim 1, characterized in that, In step S33, the parameters for pulsed ultrasonic treatment are: power of 150-180W, ultrasonic time of 2-5 min, and water temperature of 30±2℃.

6. The method for screening high-density solution-treated titanium alloy products according to claim 1, characterized in that, In step S34, the parameters for spray cleaning are: spray pressure of 0.3-0.4 MPa and spray time of 30-40 s.

7. The method for screening high-density solution-treated titanium alloy products according to claim 1, characterized in that, In step S35, the parameters for vacuum drying are: under conditions of -0.08 to 0.1 MPa and 50 to 55°C, a drying nitrogen gas with a flow rate of 1 to 2 L / min is introduced for purging, and the drying time is 10 to 15 min.

Citation Information

Patent Citations

  • Method for sorting impurities by using organic medium separation liquid

    CN113385295A